DINAMIKA PEMAAFAN (AL-‘AFW) PADA MAHASISWA MUSLIM KORBAN PERCERAIAN ORANG TUA SEJAK KECIL - Irfa Ilmatu Silvia; Triyono Triyono (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
Muslim students who experienced parental divorce during childhood tend to carry negative emotions into adulthood, which may disrupt their psychological well-being. Forgiveness (Al-‘Afw) serves as an important psychological and spiritual healing mechanism, although the process is not always easy. Therefore, this study aims to explore the dynamics of forgiveness among Muslim students who experienced parental divorce in childhood, including the psychological and spiritual processes involved, as well as the factors influencing its development. This study employed a qualitative phenomenological approach involving five informants selected through purposive sampling, consisting of four females and one male. Data were collected through in-depth semi-structured interviews and non-participant observation, and analyzed using Interpretative Phenomenological Analysis (IPA). The findings reveal that forgiveness occurs gradually, beginning with awareness of emotional wounds, followed by the decision to forgive, self-reflection and empathy toward parental limitations, as well as engagement in spiritual practices such as dhikr, du’a, and sunnah prayers. Forgiveness is reflected in behavioral changes, including improved communication and an attitude of ihsan toward parents. These findings indicate that Al-‘Afw is a transformative process that integrates psychological and spiritual aspects, while enhancing inner well-being and interpersonal relationships.